2014
DOI: 10.3389/fnhum.2014.00500
|View full text |Cite
|
Sign up to set email alerts
|

Resting alpha activity predicts learning ability in alpha neurofeedback

Abstract: Individuals differ in their ability to learn how to regulate the brain activity by neurofeedback. This study aimed to investigate whether the resting alpha activity can predict the learning ability in alpha neurofeedback. A total of 25 subjects performed 20 sessions of individualized alpha neurofeedback and the learning ability was assessed by three indices respectively: the training parameter changes between two periods, within a short period and across the whole training time. It was found that the resting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 46 publications
9
80
0
Order By: Relevance
“…This is interesting when comparing with the result from Wan et al (2014) where higher resting alpha activity was related to better learning in alpha up-regulation. Taken both studies together, we speculate that the participants with larger alpha amplitude in the eyes-closed resting state might be more difficult to down-regulate alpha.…”
Section: Discussionmentioning
confidence: 67%
“…This is interesting when comparing with the result from Wan et al (2014) where higher resting alpha activity was related to better learning in alpha up-regulation. Taken both studies together, we speculate that the participants with larger alpha amplitude in the eyes-closed resting state might be more difficult to down-regulate alpha.…”
Section: Discussionmentioning
confidence: 67%
“…All of these observations led us to speculate that the laser-induced large effect in both alpha and beta power may be a mechanistic link to tPBML1064-induced improvement and enhancement of human cognition that have been repeatedly reported in sham-controlled studies by Gonzalez-Lima et al and others in recent years (12)(13)(14)(15)28). As supporting evidence for this speculation, many studies in neurofeedback research have observed improvement of cognitive performance while the upper alpha amplitude increased (44) by neurofeedback training (44)(45)(46)(47)(48).…”
Section: Tpbml1064 Modulates Alpha and Beta Powermentioning
confidence: 61%
“…[13][14][15][16]30 As supporting evidence for this speculation, many studies in neurofeedback research have observed improvement of cognitive performance while the upper alpha amplitude increased 47 by neurofeedback training. [47][48][49][50][51] We have also noticed that prefrontal tPBM has created a dominant front-to-back pattern in both alpha and beta rhythm powers, with a few minutes delay in the beta power increase. Since there is no prior literature on such observation, one possible speculation is to attribute this pattern to tPBM-induced enhancement in large-scale brain circuits in one or more prefrontal-driven brain networks, such as the frontoparietal central executive network and the default mode network (DMN) (see Sec.…”
Section: Tpbm Modulates Alpha and Beta Powermentioning
confidence: 65%